Five‐Year Impacts of Family Stressors and Combat Threat on the Mental Health of Afghanistan and Iraq War Veterans. Issue 5 (21st August 2019) - Sanders, Wesley; Smith, Brian N.; Fox, Annie B.; Vogt, Dawne
Abstract: It has been well established that warfare‐related stress puts service members at risk for a range of mental health problems after they return from deployment. Less is known about service members' experience of family stressors during deployment. The aims of this study were to (a) evaluate whether family stressors would contribute unique variance to posttraumatic stress disorder (PTSD) and depressive symptoms above and beyond combat threat during deployment and (b) examine whether family stressors would amplify the negative effects of combat threat on postmilitary mental health 5 years postdischarge. Study participants reported their experience of objective and subjective family stressors and combat threat during deployment. Objective family stressors demonstrated unique associations with PTSD and depression symptoms and remained significant after accounting for ongoing family stressors reported at follow‐up. A significant interaction was found between objective family stressors and combat threat on PTSD symptoms, r = −.10. Although the association between combat threat and PTSD was significant for participants who reported high, B = 0.04; and low, B = 0.09, exposure to family stressors, the steeper slope for those exposed to fewer family stressors indicates a stronger effect of combat threat. Follow‐up analyses revealed that veterans who experienced high amounts of family stress and high levels of combat threat reported significantly worse PTSD symptoms than those who reported low family stress, t (256) = 3.98, p < .001. Findings underscore the importance of attending to the role that family stressors experienced during deployment play in service members' postmilitary mental health. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Impactos a largo plazo de estresores familiares y amenazas de combate sobre la salud mental de los veteranos de guerra de Afganistán e Irak ESTRESORES FAMILIARES A LARGO PLAZO EN VETERANOS Ha sido bien establecido que el estrés relacionado con la guerra pone a los miembros del servicio en riesgo a una gama de problemas de salud mental después de su regreso del despliegue. Se sabe menos acerca de la experiencia de los miembros del servicio a estresores familiares durante su despliegue. Los objetivos de este estudio fueron (a) evaluar si los estresores familiares podrían contribuir de manera única a la varianza del trastorno de estrés postraumático (TEPT) y síntomas depresivos mucho mas allá de la amenaza de combate durante el despliegue y (b) examinar si los estresores familiares pueden amplificar los efectos negativos de la amenaza de combate en la salud mental postmilitar 5 años después del alta. Los participantes del estudio reportaron sus experiencias objetivas y subjetivas a estresores familiares y amenaza de combate durante el despliegue. Los estresores objetivos familiares demostraron asociaciones únicas con TEPT y síntomas depresivos y continuaron siendo significativos después de considerar los estresores familiares en curso, reportados en el seguimiento. Se encontró una interacción significativa entre los estresores familiares objetivos y la amenaza de combate en los síntomas de TEPT, r = ‐.10. Aunque la asociación entre la amenaza de combate y el TEPT fue significativa para los participantes que informaron una alta, B = 0.04; y una baja, B = 0.09 exposición a estresores familiares, la pendiente más pronunciada para aquellos expuestos a menos estresores familiares indica un efecto más fuerte de amenaza de combate. Los análisis de seguimiento revelaron que los veteranos que experimentaron grandes cantidades de estrés familiar y altos niveles de amenaza de combate informaron síntomas de TEPT significativamente peores que aquellos que informaron un bajo estrés familiar, t (256) = 3.98, p <.001. Los resultados subrayan la importancia de prestar atención al papel que los estresores familiares experimentados durante el despliegue en la salud mental post‐militar de los miembros del servicio. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Long‐Term Impacts of Family Stressors and Combat Threat on the Mental Health of Afghanistan and Iraq War Veterans Traditional Chinese 標題: 家庭壓力源與戰鬥威脅對阿富汗和伊拉克戰爭退役軍人的心理健康構成的長遠影響 撮要: 過去的研究, 已證實戰爭相關的壓力使軍人退役後有風險患多種心理健康問題。然而, 較少有研究檢視軍人服役時承受的家庭壓力源。本研究旨在(a)評估服役時經歷的家庭壓力源, 對創傷後壓力症(PTSD)及抑鬱症狀構成的變異量, 是否獨特而且程度超於服役時經歷的戰鬥威脅所致, 及(b)檢視家庭壓力源是否會加深戰鬥威脅在退役5年後帶來的負面心理影響。樣本報告他們服役時承受的客觀與主觀家庭壓力源, 以及經歷的戰鬥威脅。客觀家庭壓力源跟PTSD及抑鬱症狀有獨特關連。而且, 我們在跟進期評估過持續的家庭壓力源後, 此關連仍然顯著。我們亦發現客觀家庭壓力源跟戰鬥威脅對PTSD症狀的影響有顯著的相互效應(r = ‐.10)。有高水平家庭壓力源(B = 0.04)和低水平家庭壓力源(B = 0.09)的樣本, 當中戰鬥威脅跟PTSD的關連都顯著;但經歷較少家庭壓力源的樣本呈現較斜的數據線, 反映戰鬥威脅有較強效應。跟進分析反映, 承受高水平家庭壓力源及高水平戰鬥威脅的退役軍人, 相比承受低水平家庭壓力源的樣本, 顯著地有較嚴重的PTSD症狀(t(256) = 3.98, p < .001)。結果凸顯, 我們有需要留意軍人服役時承受的家庭壓力源, 如何影響到軍人退役後的心理健康。 Simplified Chinese 标题: 家庭压力源与战斗威胁对阿富汗和伊拉克战争退役军人的心理健康构成的长远影响 撮要: 过去的研究, 已证实战争相关的压力使军人退役后有风险患多种心理健康问题。然而, 较少有研究检视军人服役时承受的家庭压力源。本研究旨在(a)评估服役时经历的家庭压力源, 对创伤后压力症(PTSD)及抑郁症状构成的变异量, 是否独特而且程度超于服役时经历的战斗威胁所致, 及(b)检视家庭压力源是否会加深战斗威胁在退役5年后带来的负面心理影响。样本报告他们服役时承受的客观与主观家庭压力源, 以及经历的战斗威胁。客观家庭压力源跟PTSD及抑郁症状有独特关连。而且, 我们在跟进期评估过持续的家庭压力源后, 此关连仍然显著。我们亦发现客观家庭压力源跟战斗威胁对PTSD症状的影响有显著的相互效应(r = ‐.10)。有高水平家庭压力源(B = 0.04)和低水平家庭压力源(B = 0.09)的样本, 当中战斗威胁跟PTSD的关连都显著;但经历较少家庭压力源的样本呈现较斜的数据线, 反映战斗威胁有较强效应。跟进分析反映, 承受高水平家庭压力源及高水平战斗威胁的退役军人, 相比承受低水平家庭压力源的样本, 显著地有较严重的PTSD症状(t(256) = 3.98, p < .001)。结果凸显, 我们有需要留意军人服役时承受的家庭压力源, 如何影响到军人退役后的心理健康。